Leverage Factors Affecting the Sustainability of Seaweed Agro-industry Development in Central Sulawesi, Indonesia - Alimudin Laapo; Asriani Hasanuddin; Andi Darmawati Tombolotutu (Universitas Muhammadiyah Yogyakarta, 2022)
There has been a decline in seaweed prices in Central Sulawesi in the last five years, particularly in the processing and marketing sub-systems. The processing problems have constrained the volume of market demand. In contrast, marketing problems have disturbed the fulfillment of industrial and consumer demand for raw materials, thereby declining economic activity and profit. This research aimed to examine the leverage factors affecting the sustainability of the seaweed agro-industry integrated between sub-systems in Central Sulawesi Province. The collected numerical and non-numerical data were analyzed using the multidimensional scaling approach of the RAP-Seaweed technique. The results revealed that social conflict, labor absorption, the low value-added of the seaweed processing, and the high cost of raw material procurement caused the unsustainable development of the seaweed agro-industry. Therefore, government policies are required to facilitate investment in the seaweed industry, supported by enhancing the quality of transportation infrastructure, the use of local workers, and the security stability of the local area